Molecular and thin film properties of cobalt half-sandwich compounds for optoelectronic application. Issue 9 (20th February 2017) - Reinhardt, Maxwell; Dalgleish, Simon; Shuku, Yoshiaki; Reissig, Louisa; Matsushita, Michio M.; Crain, Jason; Awaga, Kunio; Robertson, Neil
Abstract : The structure and electronic properties of two cobalt half-sandwich complexes are described in view of their potential optoelectronic device application. Abstract : The structure and electronic properties of a novel cobalt half sandwich complex of cyclopentadiene (Cp) and diaminonaphthalene (DAnap) [CpCo(DAnap)] are described and compared to the previously reported diaminobenzene derivative [CpCo(DAbnz)] in view of their potential for (opto)electronic device application. Both complexes show stable redox processes, tunable through the diaminoacene ligand, and show strong absorption in the visible region, with additional transitions stretching into the near infrared (NIR). CpCo(DAnap) crystallises with a particularly large unit cell (9301 Å 3 ), comprising 32 molecules, with a gradual rotation over 8 molecules along the long c -axis. In the solid state the balance of the optical transitions in both complexes is reversed, with a suppression of the visible band and an enhancement of the NIR band, attributed to extensive intermolecular electronic interaction. In the case of CpCo(DAnap), highly crystalline thin films could be formed under physical vapor deposition, which show a photocurrent response stretching into the NIR, and p-type semiconductor behavior in field effect transistors with mobility values of the order 1 × 10 −4 cm 2 V −1 s −1 . The device performance is understood through investigation of the morphology of the grown films.